2016
DOI: 10.1165/rcmb.2015-0036oc
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Respiratory Failure with Retarded Perinatal Lung Maturation in Mice Caused by Reticulocalbin 3 Disruption

Abstract: Reticulocalbin 3 (Rcn3) is an endoplasmic reticulum lumen protein localized to the secretory pathway. As a Ca2t-binding protein of 45 kDa (Cab45)/Rcn/ER Ca2t-binding protein of 55 kDa (ERC45)/calumenin (CREC) family member, Rcn3 is reported to function as a chaperone protein involved in protein synthesis and secretion; however, the biological role of Rcn3 is largely unknown. The results presented here, for the first time, depict an indispensable physiological role of Rcn3 in perinatal lung maturation by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…Consistently, high expression of Rcn3 in human lung tissue has also been reported by Hou Yu et al [8]. We further revealed that Rcn3 knockout mice died from neonatal respiratory distress due to the impaired maturation of alveolar epithelial type II cells (AECIIs), suggesting its potential role in regulating AECIIs function [7]. In addition, we demonstrated that the selective deletion of Rcn3 in AECIIs exacerbated bleomycin-induced lung fibrosis [9].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistently, high expression of Rcn3 in human lung tissue has also been reported by Hou Yu et al [8]. We further revealed that Rcn3 knockout mice died from neonatal respiratory distress due to the impaired maturation of alveolar epithelial type II cells (AECIIs), suggesting its potential role in regulating AECIIs function [7]. In addition, we demonstrated that the selective deletion of Rcn3 in AECIIs exacerbated bleomycin-induced lung fibrosis [9].…”
Section: Introductionsupporting
confidence: 87%
“…It belongs to the Cab45/Rcn/ERC45/Calumenin family [6], the biological function of which is still far from clear. We have previously reported that Rcn3 was expressed in a variety of mouse tissues with the highest expression in the lung [7]. Consistently, high expression of Rcn3 in human lung tissue has also been reported by Hou Yu et al [8].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, Rcn3 emerged as a new potential regulator of collagen production in vitro 27 . Rcn3 knockout mice exhibited neonatal lethality caused by impaired synthesis and secretion of surfactant in lung tissue 28 . However, the function of Rnc3 in postnatal tendon development is not known.…”
Section: Introductionmentioning
confidence: 99%
“…PS is a complex lipid and protein mixture, produced by AECIIs from late fetal development onwards, and prevents alveolar collapse by regulating surface tension at the pulmonary air-liquid interface (4). It is composed of 90% lipids and 10% surfactant-associated proteins, including surfactant protein (SP)-A, SP-B, SP-C and SP-D. SP-A and SP-D, hydrophilic collectin proteins, participate in pulmonary host defense and modify immune responses, whereas SP-B and SP-C, small hydrophobic proteins, together with dipalmitoylphosphatidylcholine (DPPC), confer surface tension lowering properties to the material (5)(6)(7). MicroRNAs (miRNAs/miRs) are a class of small non-coding RNAs that suppress gene translation, most commonly through promoting mRNA degradation or disrupting mRNA translation.…”
Section: Introductionmentioning
confidence: 99%